Testing the efficiency of plant artificial microRNAs by transient expression in Nicotiana benthamiana reveals additional action at the translational level - Yu, Shi; Pilot, Guillaume (Frontiers in Plant Science, 2014)
Artificial microRNAs (amiRNAs) have become an important tool to assess gene functions due to their high efficiency and specificity to decrease target gene expression. Based on the observed degree of complementarity between microRNAs (miRNAs) and their targets, it was widely accepted that plant miRNAs act at the mRNA stability level, while the animal miRNAs act at the translational level. Contrary to these canonical dogmas, recent evidence suggests that both plant and animal miRNAs act at both levels. Nevertheless, it is still impossible to predict the effect of an artificial miRNA on the stability or translation of the target mRNA in plants. Consequently, identifying and discarding inefficient amiRNAs prior to stable plant transformation would help getting suppressed mutants faster and at reduced cost. We designed and tested a method using transient expression of amiRNAs and the corresponding target genes in Nicotiana benthamiana leaves to test the efficacy of amiRNAs for suppression of the target protein accumulation. The ability of the amiRNAs to suppress the target gene expression in N. benthamiana was then compared to that in stably transformed Arabidopsis. It was found that the efficacy of sixteen amiRNAs, targeting a total of four genes, varied greatly. The effects of amiRNAs on target mRNAs accumulation did not always correlate with target protein accumulation or the corresponding phenotypes, while a similar trend of the silencing efficacy of amiRNAs determined between N. benthamiana and stably transformed Arabidopsis could be observed. Our results showed that, similar to endogenous plant miRNAs, plant amiRNAs could act at the translational level, a property needed to be taken into account when testing the efficacy of individual amiRNAs. Preliminary tests in N. benthamiana can help determine which amiRNA would be the most likely to suppress target gene expression in stably transformed plants.